The Repercussions of Armed Conflicts on Neighboring Countries: The Libyan Conflict as an Example - Maaziz, Abdelssalam (Journal of Legal Studies and Researches, 2022)
Any armed conflict results a number of repercussions of varying gravity on the country in question mainly, but the neighboring countries are not spared from these repercussion, and this is what this study is trying to show by demonstrating the prevailing effects that result from any conflict in the neighboring countries. Then, we review the Libyan conflict and how it had a number of impact, sometimes different and sometimes alike, especially on Algeria and Tunisia.